FAKTOR-FAKTOR YANG MEMPENGARUHI KESADARAN BERINVESTASI PADA PEGAWAI LINGKUP KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN - Ria, Fanny Roswita; Usman Bahtiar (FEB Universitas Sam Ratulangi Manado, 2024)
This study aims to analyze the Factors Affecting Investment Awareness in Employees of the Ministry of Environment and Forestry. The factors used in this study include Financial Literacy, Spending Patterns, Self-Control, Saving Behavior, Attitudes Toward Risk, Financial Socialization in the Family and Education System Support with Investing Awareness as the dependent variable. The data used in this study is primary data with the hypothesis testing method. This study uses a quantitative approach using survey research (questionnaire) as many as 60 questions with a research sample of 320 respondents. Data analysis used for hypothesis testing is simple linear regression analysis using the SPSS version 25. The results of this study indicate that Financial Literacy, Saving Behavior, Attitude Toward Risk, Financial Socialization in the Family and Education System Support have a positive and significant effect on Investing Awareness while Spending Patterns and Self-Control have no significant effect on Investing Awareness. The results also illustrate the importance of financial literacy in making decisions to invest, the higher a person's financial literacy, the higher the awareness to invest. The implication of this research is for employees of the Ministry of Environment and Forestry to pay attention to financial literacy, saving behavior, attitude towards risk, financial socialization in the family and support from the education system to influence investment awareness. In addition, for managers and financial services companies to stimulate investment intentions by publishing articles in the mass media and socialization activities. Implications for further researchers as a supporting reference.